Influence of bearing platform size on bearing capacity of NT-CEP pile group foundation under compound force - Yongmei Qian; Yuhang Li; Xun Li; Ziyu Wang; Yang Yang; Da Teng; Zhongwei Ma (Scientific Reports)
Abstract The compressive bearing capacity of a new type of concrete-expanded plate pile (NT-CEP pile) is significantly affected by the size of the bearing platform; however, research in this area remains limited. Therefore, this study investigates the effect of bearing platform size on the compressive bearing capacity of an NT-CEP pile foundation under combined vertical and horizontal loads. Using ANSYS finite element software, a four-pile model was established to analyze the failure behavior of the bearing platform and surrounding soil under these loads. The findings indicate that in an NT-CEP four-pile foundation, the bearing capacity of piles with a bearing platform increased by 66.67% compared with those without one. However, although the bearing capacity increased with platform size, this increase reduced after reaching a certain threshold. Optimal bearing performance was achieved when the platform size was 1.5 times the pile diameter from the edge to the pile center. High shear stress at the junction between the lower part of the platform and pile body suggested a potential stress concentration. The findings emphasize the importance of maintaining the optimal bearing platform size and reinforcing the connection between the platform and pile body to prevent local damage from affecting the overall bearing capacity.